The role of women in regional leadership as political communicators - Titi Sumarti, Djoko Susanto, Sa'diyah El Adawiyah, Aida Vitayala S Hubeis (Opción, 2019)
The aim of the study is to investigate the role of women in regional leadership as political communicators in making changes to constituent behavior. The research method used was qualitative with a phenomenological approach to three female heads of regions. In result, the DR from dynastic elements had characteristics higher than N and RT. The role of women leaders in the area as political communicators in local politics has much colored the local political map, both at the provincial and district/city levels, although it has not been proportional to the total number of regional heads and mandates of existing regulations.